Weight loss has an additive effect on the proteinuria reduction of angiotensin II receptor blockers in hypertensive patients with chronic kidney disease - Shin Young Ahn; Dong Ki Kim; Seung Seok Han; Jung Hwan Park; Sung Joon Shin; Sang Ho Lee; Bum Soon Choi; Chun Soo Lim; Suhnggwon Kim; Ho Jun Chin (The Korean Society of Nephrology, 2018)
Background : Weight reduction is a lifestyle intervention that has been introduced for prevention and management of chronic kidney disease (CKD). We investigate the additive anti-proteinuric effect of weight reduction on the usage of angiotensin II receptor blockers (ARBs) and its potential mechanisms in hypertensive CKD patients. Methods : This study is a subanalysis of data from an open-label, randomized, controlled clinical trial. Among the 235 participants, 227 were assigned to subgroups according to changes in body weight. Results : Fifty-eight participants (25.6%) were assigned to group 1 (≥ 1.5% decrease in body weight after 16 weeks), 32 participants (14.1%) were assigned to group 2 (1.5-0.1% decrease in body weight), and 136 participants (59.9%) were assigned to group 3 (≥ 0.0% increase in body weight). Characteristics at enrollment were not different among the three groups, but mean differences in weight and percent changes in urinary sodium excretion over the period were statistically different (P < 0.001 and P = 0.017). Over the study period, unintentional weight loss independently increased the probability of reduced albuminuria (group 1, relative risk 6.234, 95% confidence interval 1.913-20.315, P = 0.002). Among urinary cytokines, only podocalyxin level decreased significantly in participants who lost weight (P = 0.013). Conclusion : We observed that weight loss had an additive effect on the anti-proteinuric effects of ARBs in nondiabetic hypertensive CKD patients, although it was minimal. An additive effect was shown in both obese and non-obese participants, and its possible mechanism is related to reduction of podocyte damage.